EFEKTIFITAS JERUK NIPIS (CITRUS AURANTIFOLIA) DALAM MEMATIKAN LARVA NYAMUK ANOPHELES SP - Fajar Akbar; Zrimurti Mappau; Fitriani S Fitriani S (Jurnal Kesehatan Manarang, 2017)
Anopheles Sp mosquitoes around the world contain about 2000 species, while those that can transmit malaria are about 60 species. According to observations in Indonesia found 80 species Anopheles Sp, while the vector malaria is 22 species with different breeding places. This study aims to determine the effectiveness of leaf, skin, and lemon juice on the death of Anopheles Sp larvae. This study is an experimental study to determine the effectiveness of lime in deadly mosquito larvae Anopheles Sp. The samples used in this research are Anopheles Sp instar III and IV mosquito larvae. This test is done every 3 times for 6 hours and observed every 1 hour. The results of this study showed that lime by comparing leaf, skin, and lime juice for 6 hours with 20 Anopheles Sp mosquito larvae in each experiment showed that using lemon leaf solution the highest number of deaths on 6 hours observation 16,7 tail (83,5%), lemon peel solution highest average death rate at 6 hours observation as much as 19,3 tails (96,5%), and lime juice the average number of death highest at 6 hours of observation of 19 tails (95%). Based on the research results, it can be concluded that lime is able to kill Anopheles Sp mosquito larvae with effective comparison is lime skin with percentage of death of 96%. Should approach the community and socialize the potential of natural resources, in this case the use of lime as a natural larvacide to reduce the number of larval populations and can be applied as a method of overcoming malaria and can develop penilitian utilization of lime.